2016
DOI: 10.1128/mcb.00712-15
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated KLF4 Expression in Myeloid Leukemias Alters Cell Proliferation and Differentiation through MicroRNA and Gene Targets

Abstract: bAcute myeloid leukemia (AML) is characterized by increased proliferation and blocked differentiation of hematopoietic progenitors mediated, in part, by altered myeloid transcription factor expression. Decreased Krüppel-like factor 4 (KLF4) expression has been observed in AML, but how decreased KLF4 contributes to AML pathogenesis is largely unknown. We demonstrate decreased KLF4 expression in AML patient samples with various cytogenetic aberrations, confirm that KLF4 overexpression promotes myeloid differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 77 publications
0
23
1
Order By: Relevance
“…In addition, a recent study using single-cell RNA sequencing revealed high KLF4 expression during the acceleration of chronic lymphocytic leukemia (CLL) that reoccurs at relapse (24). In myeloid leukemias, low KLF4 levels were associated with altered differentiation via deregulation of gene and microRNA networks (25) and KLF4 expression inversely correlated with HDAC1 activity (26). Inducible expression of KLF4 in Jurkat cell lines and primary T-ALL cells induced apoptosis via the BCL2/BCLXL pathway (27).…”
Section: Emerging Role Of Klf4 In Hematological Malignanciesmentioning
confidence: 99%
“…In addition, a recent study using single-cell RNA sequencing revealed high KLF4 expression during the acceleration of chronic lymphocytic leukemia (CLL) that reoccurs at relapse (24). In myeloid leukemias, low KLF4 levels were associated with altered differentiation via deregulation of gene and microRNA networks (25) and KLF4 expression inversely correlated with HDAC1 activity (26). Inducible expression of KLF4 in Jurkat cell lines and primary T-ALL cells induced apoptosis via the BCL2/BCLXL pathway (27).…”
Section: Emerging Role Of Klf4 In Hematological Malignanciesmentioning
confidence: 99%
“…It has been shown that Ezh2 is required for proper B and T cell development [47] suggesting that lower Ezh2 expression would affect differentiation of both lymphocyte subpopulations, similar to the observed effect in leukemia patients. Interestingly, Ezh2 inactivation has been also observed in leukemia [48] and Klf4 may function as a tumor suppressor gene in leukemia [49]. The third gene that we observed differentially expressed in these in vitro systems was c-Kit, the SCF receptor.…”
Section: Discussionmentioning
confidence: 58%
“…Recent work revealed that miR-145, which is known to be downregulated by cisplatin in cisplatin-resistant ovarian cancer cells, also represses PD-L1 gene expression and induces T cell apoptosis in vitro [ 52 ]. It is known that the level of miR-150 is decreased in the plasma and blast cells of AML patients at diagnosis and that reintroducing miR-150 expression induces myeloid differentiation and inhibits the proliferation of AML cells [ 18 , 53 ]. Xi et al developed a novel targeted therapeutic strategy using FLT3L-guided miR-150-based nanoparticles to treat FLT3-overexpressing AML in an animal model with high efficacy and minimal side effects [ 54 ].…”
Section: Discussionmentioning
confidence: 99%